2013
DOI: 10.1007/s10815-013-0159-y
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular glutathione content, developmental competence and expression of apoptosis-related genes associated with G6PDH-activity in goat oocyte

Abstract: Purpose To associate glucose-6-phosphate dehydrogenase (G6PDH) activity in goat oocytes with intracellular glutathione (GSH) content, meiotic competence, developmental potential, and relative abundance of Bax and Bcl-2 genes transcripts. Methods Goat oocytes were exposed to brilliant cresyl blue (BCB) staining test and categorized into BCB + (bluecytoplasm), and BCB − (colorless-cytoplasm) groups. A group of oocytes were not exposed to BCB test and was considered as a control group. After maturation in vitro, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…Highly developmental competent goat BCB+ oocytes have previously been shown to increase the intracellular GSH content compared with BCB-(with low developmental competence) and control oocytes (Abazari-Kia et al, 2014). The results of the present study indicated enhancement of oocytes glutathione content linearly with increasing concentrations of royal jelly supplemented to IVM medium, which subsequently increased maturation rate.…”
Section: Discussionsupporting
confidence: 54%
“…Highly developmental competent goat BCB+ oocytes have previously been shown to increase the intracellular GSH content compared with BCB-(with low developmental competence) and control oocytes (Abazari-Kia et al, 2014). The results of the present study indicated enhancement of oocytes glutathione content linearly with increasing concentrations of royal jelly supplemented to IVM medium, which subsequently increased maturation rate.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, we examined the expression of BCL2 in this study. BCL2, as an antiapoptotic gene, has also been reported as a potential target of WT1 (Loeb 2006) and it is expressed in oocytes and embryos (Abazari-Kia et al 2014). We have found that the level of anti-apoptotic gene BCL2 was downregulated at every preimplantation stage of WT1 downregulated group, which suggests that the apoptosis induced by WT1 knockdown is mediated through WT1 in porcine oocytes and embryos BCL2 down-regulation.…”
Section: Wt1 In Porcine Oocytes and Embryosmentioning
confidence: 63%
“…Several efforts have been made to find connections between the characteristics of caprine oocytes and their apoptosis incidence as well as the influence of the latter on embryonic development. It has been shown that the diameter of healthy oocytes correlates with the incidence of apoptosis (Anguita et al, 2009), follicle size correlates with DNA fragmentation in oocytes (Romaguera et al, 2010), and glucose-6-phosphate dehydrogenase (G6PDH) activity of goat oocytes (determined by brilliant cresyl blue staining) enhances embryonic development and increases Bcl-2 expression in blastocysts (Abazari-Kia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%